Lessons from a Landscape Irrigation Rebate Program in Miami Dade County - Haimanote K. Bayabil; Laura Vasquez; Jesus Lomeli; Patrick Martin ([TEST] Journal of Extension, 2021)
We calculated savings in outdoor water uses from 37 properties in Fisher Island, Florida, that were retrofitted with smart Evapotranspiration-based irrigation controllers through the Miami Dade County’s Landscape Irrigation Rebate Program. We found average water savings of 11.4 million gallons per year from the 37 properties on the island. We discuss the roles of extension personnel in developing and effectively managing an irrigation rebate program and the implications of results from this program for large scale efforts towards efficient use of freshwater resources.
Keywords: Smart Evapotranspiration; Smart controllers; Urban irrigation; Florida Yards and Neighborhoods; Turf irrigation